Papel da Na+, K+ - ATPase no modelo de epilepsia do lobo temporal em camundongos - Funck, Vinícius Rafael (2015)
Epilepsy is a disease that affects about 1-2% of the general population. Considering the high number of patients with epilepsy who are refractory to currently available drugs, it is important to search for new anticonvulsant drugs. For this it is important that reproduces model epilepsy, such as the pilocarpine model, a muscarinic agonist causing limbic seizures and status epilepticus, which after a latency period is characterized by a temporal lobe epilepsy. A potential drug target in the treatment of epilepsy is the Na+,K+-ATPase, which is characterized by being a plasma membrane protein having important role in the maintenance of cellular ionic homeostasis, changes in the Na+,K+-ATPase activity directly affect cell signaling via neurotransmitters and neuronal activity. In this context, a impair the functioning of the Na+,K+-ATPase leads to an increased or decreased neuronal excitability, depending on the degree of inhibition induced neuronal and type affected. Therefore, the present study searched for the role of Na+,K+-ATPase and the specific antibody that enhances the activity of Na+,K+-ATPase (DRRSAb) in the pilocarpine model in C57BL/6 mice challenged with pentylenetetrazol (PTZ). It was seen that the activity of Na+,K+-ATPase was decreased in hippocampus of epileptic mice, 60 days after status epilepticus (SE). Furthermore, the Michelis-Menten constant for different ATP concentrations increased in the SE. Reduced activity of Na+,K+-ATPase appears to involve the nitration of α subunit, but no changes in the expression or its phosphorylation state at Ser943 was found. Interestingly, activation of Na+,K+-ATPase intrahippocampal injection with a specific antibody (DRRSAb) produced against a regulatory site of the α subunit, decreases susceptibility to myoclonic seizures induced by PTZ in epileptic animals. On the other hand, the administration of DRRSAb in the hippocampus of naive animals facilitated the onset of seizures induced by PTZ. Quantitative analysis of hippocampal EEG recordings revealed that DRRSAb increased the percentage of total power contributed by delta frequency band (0-3 Hz) to large irregular amplitude pattern of hippocampal EEG. On the other hand, no DRRSAb-induced changes were found regarding the theta functional state. Therefore, activation of Na+,K+-ATPase activity as a novel approach in seizure disorders, may become a potential target for epilepsy.